Can I just check...? Effects of edit check questions on measurement error and survey estimates - Peter Lugtig; Annette Jäckle (University of Essex, Institute for Social and Economic Research (ISER), 2011)
Household income is difficult to measure, since it requires collecting information about all potential income sources for each member of a household. We assess the effects of two types of edit check questions on measurement error and survey estimates: within-wave edit checks use responses to questions earlier in the same interview to query apparent inconsistencies in responses; dependent interviewing uses responses from prior interviews to query apparent inconsistencies over time. The findings suggest that traditional interviewing methods under-estimate household income in the lower tail of the income distribution, but that neither edit check method has much effect on estimated poverty rates or transition rates in poverty.
Keywords: I32; C83; 330; dependent interviewing; validation study; record check; panel survey; British Household Panel Survey; unearned income; non-labor income; cash transfer; household income; poverty; low income; Haushaltseinkommen; Messung; Einkommensverteilung; Statistischer Fehler; Befragung; Großbritannien